A simple and high-yield route to iridium, rhodium, osmium and ruthenium nido-6-metalladecaborane compounds. Issue 45 (11th November 2021) - Bould, Jonathan; Londesborough, Michael G. S.; Passarelli, Vincenzo; Clegg, William; Waddell, Paul G.; Cvačka, Josef; Macías, Ramón
Abstract : Diethyl ether is a convenient solvent for the high-yield preparation of ten-vertex metalladecaboranes that are excellent 'B-frames' for the assembly of bimetallic compounds. Abstract : We report a high-yield heterogeneous solid/liquid phase synthetic method to a series of nido -6-metalladecaboranes. The hydridoirida– and hydridorhoda–decaboranes, [6, 6, 6-H(PPh3 )2 - nido -6-MB9 H13 ] [M = Ir (1 ), Rh (2 )] are isolatable in 98% yields from the reaction of the square-planar M(i ) complexes, [MCl(PPh3 )3 ] (M = Rh, Ir), with K[B9 H14 ]. The same synthetic procedure, but using [MCl(CO)H(PPh3 )3 ] (M = Ru, Os) as metal starting reagents produces the CO-ligated clusters, [6, 6, 6-(CO)(PPh3 )2 - nido -6-MB9 H13 ] [M = Ru (3 ), Os (4 )], in yields of 83% and 95%, respectively. These highly convenient syntheses permit the investigation of the reaction chemistry of the new nido -6-metalladecaboranes. Thus, the CO-ligated compounds, 3 and 4, react with the square-planar platinum(ii ) complex, [PtCl2 (PMe2 Ph)2 ], in the presence of potassium triethylborohydride, to give the bimetallic clusters, [1, 1, 1-(CO)H(PPh3 )- isocloso -1-RuB9 H8 -μ-(1, 2)-{Pt(PMe2 Ph)2 }] (5 ) and [7, 7-(PMe2 Ph)2 -9, 9, 9-(CO)(PPh3 )2 - nido -7, 9-PtOsB9 H11 ] (6 ), and the monometallic nido -5-osamadecaborane, [5, 5, 5-(PPh3 )2 (CO)- nido -5-OsB9 H13 ] (7 ). This reactivity illustrates the potential of polyhedral boron-based clusters as molecular scaffolds ("B-frames") for the construction of multimetallic species. Single-crystal X-ray diffraction analyses have revealed the molecular structures of 3, 5, 6 and 7 ; the compounds are also studied by multielement NMR spectroscopy, mass spectrometry, IR spectroscopy, and in some cases computationally. Futhermore, the rotation of the {M(X)(PR3 )2 } moiety (X = H, CO), as PH3 -ligated models, is studied by means of DFT-calculated relaxed potential energy surface scans, giving some insight into the lability of the metal-to-borane fragment interaction and of the exo -polyhedral ligands.